1999
DOI: 10.1136/thx.54.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Avidity of anti-P aeruginosa antibodies during chronic infection in patients with cystic fibrosis

Abstract: Background-In order to study the impact on the lung function of patients with cystic fibrosis of the avidity of antipseudomonal antibodies, the avidity of antibodies against the chromosomal -lactamase of Pseudomonas aeruginosa (a ab) and against the 60-65 kDa heat shock protein of P aeruginosa (antiGroEL) were measured in serum samples collected longitudinally during chronic infection with P aeruginosa from a group of patients with poor and good lung function. Methods-Thethiocyanate elution method in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…Interestingly, this response was not seen in the sera of patients with CF. This lack of expected affinity maturation has been described previously for the humoral response to Pseudomonas aeruginosa in subjects with cystic fibrosis 31 . Whether this is related to differences in the CF host, differences in the pathogen, or differential expression of antigens during colonization of the CF lung remains unclear but warrants further investigation.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, this response was not seen in the sera of patients with CF. This lack of expected affinity maturation has been described previously for the humoral response to Pseudomonas aeruginosa in subjects with cystic fibrosis 31 . Whether this is related to differences in the CF host, differences in the pathogen, or differential expression of antigens during colonization of the CF lung remains unclear but warrants further investigation.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, and in contrast to what is usually reported during the course of an infection, there was no maturation in avidity (binding strength between antibody and antigen) of antibodies directed against chromosomal β‐lactamase of P. aeruginosa or the P. aeruginosa heat shock protein Gro‐EL during an 11‐year follow‐up period of the chronic P. aeruginosa lung infection in CF (Ciofu et al , 1999). In accordance, other investigators have reported the development of reduced opsonic killing by antibody responses directed against P. aeruginosa exopolysaccharide (Meluleni et al , 1995).…”
Section: Antibody Responses and Biofilm Infectionsmentioning
confidence: 66%
“…During chronic lung infections in affected CF individuals, high levels of antibodies against components of P. aeruginosa such as surface O-polysaccharides and mucoexopolysaccharides are present, but they have poor opsonic activity and cannot clear the infection. 9,10 Furthermore, the mucoid phenotype resists to the opsonic killing by antibodies because of the biofilm formation. 11 High antibody titers have been associated with more severe lung disease.…”
Section: Host Immune Response To P Aeruginosamentioning
confidence: 99%